The Theoretical Problem of Sources of International Law - Saganek, Przemysław (University of Wroclaw. Faculty of Law, Administration & Economics, 2018)
Sometimes the reference to sources is treated as a mere didactic introduction to the quantum of statements on treaties, custom, resolutions of international organizations and possibly some other matters. These presentations, as such, are usually very competent and valuable. However, what is often missing is a clear statement as to why the elements discussed by a given author are sources of international law, or possibly which of the elements which are discussed are not sources and why the elements absent from the list are not included as well.
Keywords: souces of international law; customary law; treaties; other sources